Strategic management of the church as challenge and reality : can the habitat of expectation solve this dilemma? - Oosthuizen, Andrè J.; Lategan, Laetus O.K. (Journal for Christian Scholarship = Tydskrif vir Christelike Wetenskap, 2016)
This paper departs from the perspective that despite the unique position of the church as a faith-based organisation, management skills and principles are required to manage the church. Following on this perspective is the position taken that an applicable strategic management process and framework are required to lead the church in achieving its strategic intent. Unfortunately, the context or habitat of the church is very often neglected in the strategic management process. The paper presents a habitat of expectation as the unique contribution to the strategic management process for the church as an organisation. The arguments are based on the premises that any strategic management process has three fundamental stages, namely analysis, implementation and evaluation. The Planning, Implementation and Checking framework (PIC-framework) is presented as a strategic management framework for the church as an organisation. Strategiese bestuur van die kerk as uitdaging en realiteit: Kan die habitat van verwagting die dilemma oplos? Hierdie artikel vertrek van die perspektief dat ten spyte van die unieke posisie van die kerk as ŉ geloofsgebaseerde organisasie, daar ŉ behoefte is aan bestuursvaardighede en -beginsels om die kerk te bestuur. ŉ Toepaslike strategiese bestuursproses en raamwerk word benodig om strategiese doelwitte te bereik. Ongelukkig word die konteks of habitat van die kerk verwaarloos in die strategiese bestuursproses. Hierdie artikel bied ŉ habitat van verwagting aan as die unieke bydrae vir die strategiese bestuursproses van die kerk as organisasie. Die argumente in die artkel berus op die aanname dat enige strategiese bestuursproses drie fundamentele prosesse het naamlik analise, implementering en evaluering. Die Beplanning (“Planning”), Implementering (“Implementation”) en Evaluering (“Checking”) raamwerk (“PIC-framework”) word aangebied as ŉ strategiese bestuursraamwerk vir die kerk as organisasie.
Published Article
Keywords: Church management; Habitat; Management of expectation; PIC framework; Strategic management process